2017
DOI: 10.1038/s41598-017-05563-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced changes in the glycome of endothelial cells with functional consequences

Abstract: As it is altered by ionizing radiation, the vascular network is considered as a prime target in limiting normal tissue damage and improving tumor control in radiation therapy. Irradiation activates endothelial cells which then participate in the recruitment of circulating cells, especially by overexpressing cell adhesion molecules, but also by other as yet unknown mechanisms. Since protein glycosylation is an important determinant of cell adhesion, we hypothesized that radiation could alter the glycosylation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
(61 reference statements)
4
35
0
Order By: Relevance
“…Very little is known about potential changes in cancer cell glycosylation related to cell behaviour following radiation. Intriguingly, however, Jaillett et al (2017) showed overexpression of several polypeptide-N-acetylgalactosamine (GalNAc) transferases (GalNAc-Ts), the family of genes that mediate the attachment of the first GalNAc in O-linked glycosylation, by endothelial cells, in mouse intestine after radiation exposure [111]. As described previously, cancer cells frequently exhibit an increase in truncated O-glycans consistent with this type of general up-regulation in O-linked glycosylation.…”
Section: The Effect Of Radiation On Normal and Cancer Cell Glycosylationmentioning
confidence: 70%
See 1 more Smart Citation
“…Very little is known about potential changes in cancer cell glycosylation related to cell behaviour following radiation. Intriguingly, however, Jaillett et al (2017) showed overexpression of several polypeptide-N-acetylgalactosamine (GalNAc) transferases (GalNAc-Ts), the family of genes that mediate the attachment of the first GalNAc in O-linked glycosylation, by endothelial cells, in mouse intestine after radiation exposure [111]. As described previously, cancer cells frequently exhibit an increase in truncated O-glycans consistent with this type of general up-regulation in O-linked glycosylation.…”
Section: The Effect Of Radiation On Normal and Cancer Cell Glycosylationmentioning
confidence: 70%
“…They found an increase in high-mannose or oligomannose type N-glycans (these are glycans where the trimannosyl core is extended by mannose residues exclusively) and an increase in monocyte adhesion to endothelial cells, but were unable to demonstrate that the glycans were functional in this adhesion. They suggested that alterations in glycosylation may be a mechanism by which organisms regulate cell adhesion during inflammation, recovery, and healing after radiation exposure [111].…”
Section: The Effect Of Radiation On Normal and Cancer Cell Glycosylationmentioning
confidence: 99%
“…Within these matured and normal vessels endothelial anergy is restored. Jaillet et al reported that ionizing radiation altered the glycosylation pattern of endothelial cells, in particular increased high mannose-type N-glycans and decreased glycosaminoglycans, which stimulated the interactions between irradiated endothelial cells and monocytes ( 108 ). Thus, targeting either the endothelium glycome may be considered as therapeutic target for modulating the inflammatory response or combining radiation therapy that seems to reduce endothelial anergy with anti-immunosuppressive therapy.…”
Section: Tumor Endothelium Mediated Immunological Consequences In Thementioning
confidence: 99%
“…Lee et al confirmed that radiation exposure enhanced the sialylation of cellular proteins in colon cancer cells by fluorescence- activated cell sorting analysis 27 . Analyzing site-specific data of patients suffering from head and neck cancer, Toth et al observed that intensity of 44% of glycoforms increased and 56% decreasedin in the course of radiotherapy 24 .Targeted transcriptomic approaches in vitro in endothelial cells and in vivo in a radiation enteropathy mouse model proved that genes involved in N- and O-glycosylation were altered by radiation 28 . In our work, mRNA and protein expression of C1GalT1 was induced by exposure to a low dose of radiation.…”
Section: Discussionmentioning
confidence: 99%